Analysis Of The Effect Of Marketing Mix On The Competitive Advantage Of Samoto Products In PT. Utama Netindo Semesta - Ihdina Gustina; Dedy Lazuardy; Sienny (Jurnal Manajemen Bisnis Eka Prasetya, 2022)
This study aims to determine the effect of Product and Price on the Competitive Advantage of Samoto's Products at PT. Main Netindo Semesta. The research population that will be used in the study are all consumers who made purchases on Samoto stabilizer products during the 2020 period as many as 2,905 consumers. The sample that will be used in this research is 97 consumers. The results of the research analysis show that Product and Price simultaneously have a significant influence on Competitive Advantage at PT. Main Netindo Semesta. For the coefficient of determination, it is found that Product and Price can explain its relationship with Competitive Advantage at PT. Main Netindo Semesta.